1998
DOI: 10.1038/sj.ijo.0800583
|View full text |Cite
|
Sign up to set email alerts
|

Fasting gall bladder volume and lithogenicity in relation to glucose tolerance, total and intra-abdominal fat masses in obese non-diabetic subjects

Abstract: OBJECTIVE: To investigate whether total body fat mass or fat distribution and associated metabolic disturbances in glucose and lipid metabolism in¯uence the well known gallstone pathogenetic factors in obese subjects in order to explain why some obese subjects develop gallstones and some do not. DESIGN: Cross sectional study of gallstone pathogenetic factors, body composition, fat distribution, glucose and lipid metabolism. SUBJECTS: 57 healthy overweight subjects (aged 26±64 y, body mass index (BMI) 30±45 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…2,4,6,[25][26][27] In contrast, only a few studies have focused on the association between gallbladder motility and body weight, BMI, body fat distribution, and serum lipid levels, and results have been conflicting. 1,7,8,17,18,28 Petroni 1 and Acalovschi and Badea 7 reported good correlations between fasting gallbladder volumes in obese subjects and body weight and BMI. Masclee et al 8 also reported correlations between fasting gallbladder volumes and BMI; we found a positive correlation in the present study.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…2,4,6,[25][26][27] In contrast, only a few studies have focused on the association between gallbladder motility and body weight, BMI, body fat distribution, and serum lipid levels, and results have been conflicting. 1,7,8,17,18,28 Petroni 1 and Acalovschi and Badea 7 reported good correlations between fasting gallbladder volumes in obese subjects and body weight and BMI. Masclee et al 8 also reported correlations between fasting gallbladder volumes and BMI; we found a positive correlation in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…Gallstone disease has been reported to be significantly associated with BMI, waist-to-hip circumference ratio, high triglyceride level, and low high-density lipoprotein cholesterol level. 2,4,6,[25][26][27][28] In studies evaluating only small gallstones, which may have been newly formed, a positive association between gallstones and both low-density lipoprotein cholesterol and total cholesterol levels has been reported. 2,4,6,[25][26][27] In contrast, only a few studies have focused on the association between gallbladder motility and body weight, BMI, body fat distribution, and serum lipid levels, and results have been conflicting.…”
Section: Discussionmentioning
confidence: 95%
“…They concluded that subcutaneous fat as a component of central adiposity is also an important independent marker of insulin resistance in obesity. A relationship between fat distribution, glucose tolerance, and gallstone pathogenic factors was also demonstrated in obesity with the direct measurements of fat mass by DXA (56). Therefore, DXA is a practical, widely available and precise tool for the measurement of body composition.…”
Section: Body Composition By Dxamentioning
confidence: 99%
“…Contractility of gallbladder is known to be decreased in fatty gallbladder disease [7,9]. This is induced by abnormal wall structure and decreased response of gallbladder to the neurotransmitter associated with oxidative stress and insulin resistance [10][11][12].…”
Section: Introductionmentioning
confidence: 99%